(untitled) (Research, Society and Development, 2022)
Objective: to map the literature on educational technologies developed to tackle obesity in adolescence. Methodology: guided scoping review as proposed by the Joana Briggs Institute and using the extension of the PRISMA-ScR checklist. The guiding question was: What are the existing technologies for health education for adolescents with obesity? Searches were performed on PubMed databases; Science Direct and Web of Science by the Portal of Periodicals of the Coordination for the Improvement of Higher Education Personnel (CAPES); BDENF, LILACS and Medline through the Virtual Health Library (VHL). High precision search strategies will be applied, with support from the Medical Subject Heading (MeSH) and Health Sciences Descriptors (DeCS), as well as the use of Boolean operators. The selection of studies will be made by two researchers independently. For the results, EndnoteWeb will be used in order to properly manage the references and the organization of the data will be carried out through the Microsoft Excel R program for interpretation and writing of the study results.